Climatological changes in the African intertropical zone during the last 165,000 years - (:unkn) unknown (My University, 2011)
Core KZai02 from the Zaire/Congo deep sea fan runs from MIS 6.6 to Present (last 1685 ka). Its pollen study allows to reconstruct the vegetation past variations over the Central Africa. These results, compared to the Total Organic Carbon content (TOC) and the Ti/K ratio, inform on the past trade winds and West African monsoon variability, respectively. During glacials, low temperatures over the Zaire/Congo watershed prevented the development of the tropical rain forest in opposition to savannah. Each interglacial starts with the development of mangrove testifying to events of sea-level rise. Then, the succession of grassy and forested environments indicates a gap between temperature and humidity rises. During the warmer episodes, rain forest expanded over the Central Africa. The Marine Isotope Stage 5 includes two cooler events supported by expansion of the afromontane forest (mainly Podocarpus) corresponding to substages 5b and 5d. Eccentricity, obliquity and particularly precession are identified in variations of the ecological groups of the KZai 02 pollen record and interpreted in terms of variations of precipitations linked to fluctuations of the ITCZ. Sub-Milankovitch periods are also revealed by spectral analysis and related to (1) the Heinrich and Dansgaard/Oeschger glacial pulsation events and (2) high frequency variations similar to the East Asian monsoon oscillations controlled by ice sheets
Keywords: African Research